Tourism Potential Analysis through Community-Based Tourism Approach: Talang Mamak and Melayu Tua Tribe Communities in Rantau Langsat Village - Beni Ismarizal; Elly Malihah; Rini Andari (Universitas Pendidikan Ganesha, 2023)
The purpose of this study is to identify the tourism potentials of the Talang Mamak and Melayu Tua who live in the Taman Nasional Bukit Tiga Puluh (TNBT) area of Rantau Langsat village to be developed through a Community-Based Tourism (CBT) approach. This study employs a rationalistic methodology of the qualitative descriptive variety. This study used analytical techniques with two main stages, namely content analysis and qualitative descriptive study, to achieve the research objectives. The results obtained are the three existing attractiveness factors, both natural beauty, community culture, and tourism activities, that have the potential to be developed through the CBT approach. This research can provide in-depth information about the possibility of the Talang Mamak and Melayu Tua people who live in the TNBT area of Rantau Langsat village. Then the results of these findings can become the basis for research in the development of CBT by the community and stakeholders.